Theoretical and Empirical Reflection Study of the Effect of Information Technology Implementation on Individuals, Employees, and Organizational Performance - Deddy Kusbianto, Rudy Ariyanto, Indra Dharma Wijaya (International Conference on Industrial Revolution for Polytechnic Education, 2019)
In Indonesia, the practice of performance measurement is carried out for the MPR statement TAP No. IX / MPR / 1998 concerning the implementation of regional governments that are free from corruption, collusion and nepotism and Law No. 28 of 1999 concerning the same thing. Responding to this mandate, Presidential Instruction No. 7/1999 concerning accountability for government performance requires all government institutions to formulate strategic strategies, measure performance and report as a form of accountability. Indonesian citizens need to conduct research related to the representation of information technology on the performance of individuals, employees. The analytical method used in this study reflects various very basic documents. The results of this study indicate that management involvement factors, user technical capabilities, and the usefulness of information technology systems are very important for employees, employees, and organizations.